Implementation of Reed-Solomon RS(255,239) Code - Maja Malenko (Proceedings of the International Conference on Applied Innovations in IT, 2014)
In this paper the construction of Reed-Solomon RS(255,239) codeword is described and the process of coding and decoding a message is simulated and verified. RS(255,239), or its shortened version RS(224,208) is used as a coding technique in Low-Power Single Carrier (LPSC) physical layer, as described in IEEE 802.11ad standard. The encoder takes 239 8-bit information symbols, adds 16 parity symbols and constructs 255-byte codeword to be transmitted through wireless communication channel. RS(255,239) codeword is defined over Galois Field GF( and is used for correcting up to 8 symbol errors. RS(255,239) code construction is fully implemented and Simulink test project is constructed for testing and analyzing purposes.